Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dimediasi Kesiapan Untuk Berubah - Vandani Yuraida; N. Rachma; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to analyze the effect of transformational leadership on employee performance at UMKM NILAKANDI Catering in Sidoarjo Regency mediated by readiness to change. The population used is all employees, amounting to 169 people. While the sample used in this study because it uses a saturated sampling technique, the sample taken is all 169 employees. The analytical tool used is multiple linear regression and using a questionnaire as a data collection technique.Through this research, it can be concluded that leadership and readiness to change have a direct and significant influence on employee performance, transformational leadership is able to provide a direct and significant influence on readiness to change, transformational leadership does not indirectly have a significant effect on employee performance of UMKM NILAKANDI Catering Sidoarjo Regency through readiness to change as a mediating variable.Keywords: Transformational Leadership, Readiness to Change, Employee Performance